Exploring the Phenomenon of Interfaith Marriage with an Emphasis on the Lived Experiences of Women in Iran: An Interpretative Phenomenological Study - Habibi, Elham; Torkaman, Farah; Hazrati Someeh, Zahra (Psychology of Woman Journal, 2025)
Objective: This study aims to explore the phenomenon of "interfaith marriage" from the perspective of the lived experiences of women belonging to different religious affiliations.Methods and Materials: Utilizing the interpretative phenomenological approach and Strauss's grounded theory methodology, 18 in-depth qualitative interviews were conducted. Data were analyzed through three stages of open, axial, and selective coding using ATLAS.ti software (version 7), resulting in the development of a theoretical model for women.Findings: The findings indicate that in Iranian society, factors such as individual criteria for spouse selection, religious pressures to encourage intra-faith marriage, individual religiosity and familial religiosity, acceptance and confrontation by families and friends, and the expansion of awareness and social connections contribute to women's selection of interfaith marriage. Additionally, factors such as premarital familiarity, age at marriage, and gender also influence this process. Women encounter various strategic actions and reactions, leading to the formation of four strategies: individual religious choice and acceptance of differences with respect, resolving conflicts by defining a new narrative of interfaith interaction, disregarding religion in marital life, and migration.Conclusion: The study's findings reveal that interfaith marriage results in both positive and negative outcomes.